ANALISA PENYEBAB TERJADINYA KONFLIK HORIZONTAL DI KALIMANTAN BARAT - Hadiyanto, Alwan (Universitas Riau Kepulauan, 2014)
Indonesia is a multiethnic country that protects its citizen to live in peace in every part of the republic of Indonesia as stated in UUD 1945 and UU No.39/1999. However, horizontal conflict is easily emerged as the accumulation of cultural diversities and social jealousy of local people towards outsiders economics achievement in their area. This study is done in July 2004 which means to find out the cause of horizontal conflict between Dayaks and Madurese and how to handled it.